TINDAK PIDANA PENGANIAYAAN YANG DISERTAI DENGAN PERKOSAAN DAN PENCURIAN YANG DILAKUKAN OLEH ANAK MENGAKIBATKAN MATINYA PARA ANAK KORBAN: (Studi Kasus Perkara Nomor : 25/PIDSUS.AN/2014/PT.SBY) - Prihasti, Lila Yurifa (Jurnal Panorama Hukum, 2018)
Child is a part of which do not be locked out of man viability and continuity of one nation and state, in Indonesian constitution explicit being declared that country secures each child be entitled to viability, grow up and amends and be entitled to protection of violence and discrimination. The best interest of the child have precedence over, as affirmed in Convention on the Rights of the Child, Declaration of United Nation concerning on the Rights of the Child year 1959 and in The Beijing Rules ratified through Decision of President Number 36 Year 1990 About Authentication of Convention on the Rights of the Child. Thereby, hence child conducting an injustice do not be viewed as a criminal, but have to be seen as one who need aid, affection and congeniality and also imposition of criminal law sanction to child as perpetrator of doing an injustice shall be more major approach of psychological and persuasive-educative approach. Penalization system for a child have set clear in Code Number 11 Year 2012 about Code of Child Criminal Justice System or known as UUSPPA, One of the alternative in handling child case by using diversion concept and restorative justice. Restorative justice is an approaching that emphasizes on recover loss that evoked by crime where all party in concerned in a certain doing an injustice together solve problem, creating an obligation to make everything become better by entangling child as perpetrator of doing an injustice, victim child, and society in searching solution to improve, reconciliation and liver which is do not pursuant to retaliation. But it turns out in practice, diversion concept and restorative justice not always can be applied to the case as writer have been wrote in this research. Based on the results of research can be concluded that every child of a criminal act must have a caused and harmony in the family shape the personality and character of the child.